Total Metacarpal Reconstruction with Fascia-Wrapped Fibular Graft Following Ewing Tumor Resection in a Growing Patient - Samer Abdel Al, MD; Muhamad A. Al-Qawasmi, MD; Muntaser Abu Shokor, MD; Hamza M. Khalaf, MD; Mohammad A. Alattar, PT (Journal of Hand Surgery Global Online)
Ewing tumor, a rare bone tumor, exceptionally affects the hand. We report a unique case of this tumor in the fourth metacarpal of a young patient. Reconstructing a digit after complete metacarpal removal because of sarcoma resection is a complex challenge, especially in growing individuals. We employed a novel technique involving a nonvascularized fibular autograft wrapped in fascia and intricate soft tissue reconstruction for proximal phalanx growth. The patient’s function remained satisfactory for more than 2-year follow-up.